Experimental study of mortar incorporating nano-magnetite on engineering performance and radiation shielding - Kunchariyakun Kittipong; Sinyoung Suthatip; MacKenzie Kenneth J. D.; Pungkun Vithit; Raknarong Pakkamai; Teh Musofpar; Jekabaso Afham; Sittichan Narumol (Nanotechnology Reviews)
Here, this study reports the effect of nano-magnetite (nano-Fe3O4) on the γ and neutron-radiation shielding properties of mortar using 1–10 wt% additions of nano-Fe3O4. The results indicate that nano-Fe3O4 additions enhance the radiation-shielding properties of the mortar as a result of pore filling and nucleation effects. The mortar incorporating nano-Fe3O4 exhibited relatively high compressive strength values at 28 and 90 days compared to the control mixture (NFC0). A 5 wt% addition of nano-Fe3O4 provided the best physical (1,847 ± 19.1 kg m−3), compressive strength (216.79 ± 6.19 ksc at 28 days), and radiation shielding properties, increasing the photon linear attenuation coefficient to 0.155 cm−1 from 0.144 cm−1 in the material without nano-Fe3O4. This 5 wt% addition of nano-Fe3O4 also increased fast neutron removal cross-section (ΣR) of neutrons from 0.1109 cm−1 in the control sample to 0.1192 cm−1. These results indicate that the addition of nano-Fe3O4 to radiation-shielding mortar can potentially attenuate gamma rays rather than neutrons and lead to the development of materials for shielding radiation from radioactive storage facilities, thereby reducing the impact of this hazardous waste on humans and the environment.